Interdisciplinary Place-Based Learning in Urban Education Exploring Virtual Worlds (Springer International Publishing, 2018)
This book focuses on the interdisciplinary incorporation of place-based learning in faculty teaching strategies at the New York City College of Technology. Contributing authors highlight their creative use of the unique urban environment of Brooklyn, illustrating the integration of urban resources into student research projects and activities in the context of an interdisciplinary course. Beginning with a reflection on the interrelationship between learners and nature, built and virtual environments, contributors then examine the experience of students and faculty in interdisciplinary projects in architecture, the geosciences, economics, computer science, the humanities and medicine. The volume concludes with a synthesis of best practices from these projects, focused on virtual place-based learning. This scholarly book makes a valuable contribution to the literature, offering a model of creative employment of urban spaces to enhance experiential interdisciplinary learning and demonstrating the potential educator application in diverse urban institutions elsewhere.